Resepsi Sastra Naskah Drama Kau Tunggu Siapa, Nilo Karya Wisran Hadi - Fitri, Novia Surga; R., Syahrul; Zulfadhli, Zulfadhli (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this studyis to describe the intelligent reader reception (in this study is senior student of Indonesian and Region Language and Literature Department, Padang State University) of the characterization in the script drama Kau Tunggu Siapa, Nilo work of Wisran Hadi. The data in this study is the answer (reception), the reader is contained in the statement list and the questionnaire. Sources of data in this study is that there is this statements and question in the statements list and the questionnaire submitted to the reader. The findings of the study, 20 data based on 20 statements in the statements list, and 10 data based on 10 questions in questionnaire. Once the data is obtained, the data were analyzed qualitatively using descriptive methods, and classified according to the theory used.